Kajian Pemanfaatan Cangkang Sawit Sebagai Pengganti Solar Industri Pada Sistem Thermal Oil Heater di Pabrik Resin - Dina , Sari Farah; Hutajulu, Poltak Evencus; Nur, Taufiq Bin; Karo-karo, Justaman Arifin (REACTOR: Journal of Research on Chemistry and Engineering, 2022)
The National Energy Policy to develop the use of renewable energy has opened up opportunities for industry to develop the use of biomass. A study on the use of palm shells as a substitute for industrial diesel in a thermal oil heating system at a natural rubber resin factory in North Sumatra has been carried out. All information and data on the operation of TOH were obtained through secondary data collection and direct discussions in the field. The secondary data obtained include the type and specification of the heater, the characteristics of the thermal oil (type, flow rate, temperature inlet and outlet of the heater), fuel consumption/hour and the characteristics of palm shells. From the study conducted, it can be concluded that during the process of heating thermal oil which takes place gradually in the TOH system using industrial diesel, it has a heat capacity of 1.500.000 kcal/hour, but the maximum heat that is useful for heating thermal oil is 694,396 kcal/hour with maximum thermal efficiency is 80.69%. Estimated consumption of palm kernel shells required to heat thermal oil on the assumption of 70% thermal efficiency as a substitute for energy supplied by industrial diesel is 237 kg/hour. The savings from this fuel replacement is estimated Rp.3.286.800.000/year.